An Evaluation of the Implementation of Islamic Family Law in Divorce: Between Normative Ideals and Practical Realities - Sri Wulandari; Sutra Saldi; Kurniati Kurniati (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Divorce is a social and legal phenomenon that reflects the failure of marital harmony and the inability to achieve the Islamic ideal of a sakinah, mawaddah, and rahmah family. In Indonesia, particularly in urban areas such as Makassar, divorce rates continue to increase and raise serious concerns regarding the protection of women’s and children’s rights after marital dissolution. This study is situated within the context of the high number of divorce cases in Makassar, South Sulawesi, where mediation mechanisms mandated by law have not significantly reduced divorce rates. The objective of this research is to evaluate the implementation of Islamic family law in divorce cases by examining the effectiveness of court-annexed mediation, judicial considerations, and the preventive role of the Marriage Advisory Board (BP4), as well as exploring Islamic legal alternatives such as tahkim (arbitration). This research employs a qualitative socio-legal approach, combining normative legal analysis of Islamic law, statutory regulations, and court decisions with empirical data obtained from divorce statistics, mediation records, and field observations in Makassar, particularly in Kelurahan Pannampu. The findings reveal that despite the mandatory application of mediation under Supreme Court Regulation No. 1 of 2016, the success rate of mediation in the Religious Court of Makassar remains very low. Divorce cases, especially wife-initiated divorces, continue to dominate court proceedings. Furthermore, preventive efforts through BP4 counseling programs have been implemented but face limitations in terms of resources, coordination, and effectiveness. This study concludes that there is a significant gap between the normative ideals of Islamic family law and its practical implementation, highlighting the need to strengthen alternative dispute resolution mechanisms such as tahkim and to enhance institutional synergy in order to better protect family integrity and post-divorce rights.